Development of packaging appearance element design of dadih with Kansei Engineering approach - Delfitriani, Delfitriani; Djatna, T; Syamsir, E (Institut Teknologi Sepuluh Nopember, 2018)
The appearance of a product influences consumer product choice in several ways. The concern of appearance packaging is necessary to encourage consumers to be more interested to consume the Dadih. Hence, improved Dadih packaging is expected to expand its market, extend the shelf life, and ease in consumption. Kansei engineering (KE) is defined as a technology that translates consumer’s feeling into design specifications. By using KE, we focused on analyzing and designing product and packaging appearance element design of Dadih based on consumer preferences. This paper was conducted to determine the requirement typical Dadih product main features packaging appearance element design by using KE. In order to determine the requirement typical Dadih product main features, Principal component analysis (PCA) was used as the methods to determine the product and packaging appearance element design. The result showed design support to find out the optimal combination product form element in term of sets of given product strategies. Finally, it was expected that using this methods will obtain optimal formulation on design of Dadih product on each personality type, so as to product attractive, innovative, preferred Dadih by consumer as well as minimize the risk of failure of new product design on the market.